The Influence of E-WOM on Goodreads Toward Book Purchase Intention Using the IACM Model - Muhammad Shafiq Indrawan (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The rapid expansion of information technology has strengthened electronic word-of-mouth (eWOM) as a key information source shaping consumers’ purchasing decisions. In the book market, Goodreads facilitates the exchange of reader reviews and recommendations; however, the mechanisms through which users accept such information and develop online purchase intentions remain insufficiently understood. This study aims to examine the influence of eWOM on Goodreads users’ online book purchase intention using the Information Acceptance Model, which comprises information credibility, information usefulness, attitude toward information, information adoption, and online purchase intention. A quantitative survey was conducted involving 406 Goodreads users selected through purposive sampling. Data were analyzed using partial least squares structural equation modeling with SmartPLS. The findings indicate that eight of the nine proposed hypotheses were supported. Information credibility positively influenced information usefulness, information adoption, and online purchase intention. Information usefulness positively influenced attitude toward information and information adoption but did not significantly influence online purchase intention. Attitude toward information positively influenced information adoption and online purchase intention, while information adoption positively influenced online purchase intention. These results demonstrate that information credibility, attitude toward information, and information adoption are the principal determinants of Goodreads users’ online book purchase intention, whereas information usefulness contributes indirectly through the information acceptance process. The study concludes that credible and positively evaluated eWOM is more likely to be adopted and translated into purchase intention. These findings extend the application of the Information Acceptance Model to digital book consumption and provide practical implications for authors, publishers, booksellers, and platform managers seeking to strengthen the credibility, relevance, and persuasive value of online book reviews.